(3HQfGeL bGFe Ydi eSQMI GdefGgL dHYV eLGdGJ QjGV GdCWaGd dJfejI GdJacjQ GdEHOGYi dOi Wad GdQhVI (B/ s - (3fhQG QeVGf YHOGdMejO eMehOs; (3LjgGf YHOGdaJGM YRGe (B: s; (3YdG MSf cGed (B: s ((3GdbGgQI (B: s (3fhQG QeVGf YHOGdMejO eMehO (B: s, 2021)
(3GdJMbb ef aGYdjI eSQMI GdefGgL ai Jfejg GdJacjQ GdGHOGYi dWad GdQhVg ef NdGd GdEYJeGO Ydi GdefgL GdJLQHi Ph GdeLehYJjf GdJLQjHjI h GdVGHWI(B. (3COhGJ GdOQGSI(B: (3GSJNOeJ GdHGMKI GdCOhGJ GdJGdjI(B. (3ebjGS GdJacjQ GdEHOGYi GdeUhQ dWad GdQhVI EYOGO (B/ (3GdHGMKI(B. (3HWGbI edGMXI SdhcjGJ GdCWaGd GdeQJHWI (B"(3HegGQGJ GdJacjQ GdEHOGYi EYOGO (B/ (3GdHGMKI(B. (3GdHQfGeL GdbGFe Ydi eSQMI HYV eLGdGJ QjGV GdCWaGd dJfejI GdJacjQ GdEHOGYi EYOGO (B/ (3GdHGMKI(B. (3fJGFL GdOQGSI(B: (3aGYdjI eSQMI GdefGgL ai Jfejg GdJacjQ GdGHOGYi dWad GdQhVgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI ddWahdI GdeHcQI (B- (3bSe GdYdhe GdCSGSjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJacjQ GdEHOGYis; (3Wad GdQhVIs; (3eSQMI GdefGgLs